Práticas discursivas e processos de hegemonização: o currículo-ensino de história na crise de percepção da contemporaneidade - Macedo Neto, Manoel Pereira de (2015)
The crisis of perception, the tensions and the negotiations that education concerns, specially the teaching curriculum of History in Basic Education, has assumed great relevance in the Brazilian educational system agenda in the beginning of this century. This doctoral study is included in this debate and defends the argument that the teaching curriculum of History is contributing for the hegemony of the worldview of the linear modernity. Besides, it claims that the values and concepts that constitute the linear and unidimensional thinking of modernity are not sufficient to comprehend the complexity of our days. Based on this finding, an effort to analyze policies of the teaching curriculum considering the post-struturalist debates was made. Specially, the concepts developed within the Theory of Discourse of Ernesto Laclau and Chantal Mouffe (1987); and from the dialogues with the Theory of the Complexity of Edgar Morin (1996; 2011) and the Post-Colonial studies of Homi Bhabha (2001). Considering that education and curriculum are discursive practices, this research elected the significants: “subject”, “identity”, “time”, “place” and “cross-cultural exchanges”, and, with the mediation between them, interpreted the meanings produced in the context of the teaching curriculum of History. In order to make the analytical procedures of this study feasible, the discursive corpus of the research was composed by the PCNEM (BRASIL, 2000), the PCN+ (BRASIL, 2002), the DCNEM (BRASIL, 2012), the OCEM (BRASIL, 2006), the Curricular References for High School from the State of “Paraíba” (RCEM-PB, PARAÍBA, 2006). As well as, the Framework of the National Examination for High School (ENEM), and the interviews with four teachers and four students of History from senior High School groups from two schools in the city of “João Pessoa”. The research based the thesis on the teaching curriculum of History inserted in the crisis of perception of the contemporaneity and subjected to permanent negotiations and displacement of meanings. Regarding it, this work contributes for the hegemony of distinct worldview of linear modernity.